The association of self-reported diabetes with impaired social functioning in low-, middle- and high-income countries: findings from the World Health Survey - Loerbroks, Adrian; Herr, Raphael (Diabetic medicine, 2018)
Aim Epidemiological studies from high-income countries show that diabetes is associated with impaired social functioning. As healthcare systems in middle- and low-income countries offer fewer resources to curtail the potential social impact of diabetes, we performed a comparative study on the diabetes-social impairment link in low-, middle- and high-income countries. Methods We use data from the cross-sectional World Health Survey (n = 235 428 from 10 low-income, 29 middle-income and 9 high-income countries). Diabetes was defined by self-reports of a diagnosis. Impaired social functioning was considered present if participants reported severe or extreme difficulties with personal relationships or participation in the community. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) in the overall sample and by income regions. ORs were corrected for demographics and health-related lifestyles, and then additionally adjusted for impairments that may explain any observed association (i.e. impaired vision, mood, cognition and mobility). Results In the overall sample, we confirmed an association between self-reported diabetes and impaired social functioning (OR = 1.47, 95% CI = 1.18-1.83). The strength of that relationship increased with decreasing country income (e.g. OR in low-income countries = 2.23, 95% CI = 1.14-4.37). Associations were substantially attenuated by further correction for impairments, in particular mood problems, in the overall sample (OR = 0.92, 95% CI = 0.72-1.16) and all income regions. Conclusions Self-reported diabetes is associated with impaired social functioning in high- and middle-income countries, and this relationship is even stronger in low-income countries. Associations are largely explained by physical and mental impairments, which may be due to diabetes.
Gesehen am 09.07.2020